Nigeria's public service and new public management reform / Ahmad Sanusi and Abubakar Abdullahi - Sanusi, Ahmad; Abdullahi, Abubakar (Universiti Teknologi MARA, Shah Alam, 2011)
The seeming failure of public service in Nigeria is demonstrated by a series of reforms introduced by successive governments to redefine and reinvigorate it. While some of these reforms are internal, some were externally induced. The climax of such reform initiatives in contemporary democratic Nigeria was the introduction of New Public Management commonly known as NPM. New Public Management reforms offer many alternatives towards efficient service delivery. However, because of its market-cum-democratic characteristics, it seems very difficult to operate in an unstable democratic system. Premised on the apparent desire to achieve efficient service delivery, Nigeria implemented New Public Management reform as a catalyst to redefining and retransforming its public service. This paper investigates the implementation of NPM in Nigeria and argues that minimal if any results are likely to be achieved. This is largely because of the inherent contradictions between the main requirement of NPM and the structure and the context of Nigeria's public service and its political system. Putting it in another way, the features of NPM are at variance with the main structure and the character of Nigeria's political environment. From the period of active colonialism up to today, the government has set up different public service review commissions to restructure, invigorate and reorganize the battered public service but her dream is yet to become a reality.